PENGARUH JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI KOTA LHOKSEUMAWE - Nanda Fitri Yenny; Khairil Anwar (JURNAL EKONOMIKA INDONESIA, 2020)
This research was conducted in Lhokseumawe City and the aim is to see the effect of population on economic growth in the city of Lhokseumawe. The data used in this research is secondary data sourced from the Central Statistics Agency (BPS) for 18 years from 2001-2018. The data analysis method used in this research is simple linear regression. The results of this study indicate that the population variable does not have a negative effect on population growth and the magnitude of the influence of the population variable on economic growth is 0.0938 (9.38%).